Sodium ion poly-cathode and anode material synthesized by solid phase method and preparation method of sodium ion poly-cathode and anode material
Synthesis of sodium ferric fluorine phosphate (NFPF) as the positive electrode material of sodium ion battery through solid phase method, solving the problem of insufficient magnification and cycling performance of NFPP materials, achieving higher conductivity and better cycling stability, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202411790403.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery positive electrode material NFPP has low intrinsic conductivity and heterogeneous defects during synthesis, resulting in poor rate performance and cycle performance, limiting its commercial application.
Sodium ferric fluorine phosphate (NFPF) was synthesized as sodium ion polycathode material by solid phase method. By introducing the interaction between F and Fe, structural stability is enhanced, and the crystal band gap is reduced through the P-F structure to improve the probability of electron transition.
It improves the ion and electron conductivity of NFPF, improves its rate performance and cycling performance, making it more suitable for large-scale production and commercial applications.
Smart Images

Figure CN119601655A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a sodium-ion polycathode positive electrode material synthesized by a solid phase method and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have many advantages such as high energy density, high energy conversion efficiency, and long cycle life. They have been widely used in the field of consumer electronics and power energy storage. However, the abundance of lithium in the earth's crust is low, and the distribution of lithium resources is extremely uneven (70% is distributed in South America). Sodium-ion batteries have a similar working principle to lithium-ion batteries, and the abundance of sodium in the earth's crust is 400 times that of lithium. They are widely distributed (existing in large quantities underground, in salt lakes, and in the ocean), and the development technology is mature. Compared with lithium-ion batteries, they have potential significant advantages in cost, safety performance, charge and discharge rate, environmental adaptability, etc., and have broad application prospects in energy storage and small power.
[0003] Sodium ion cathode materials are the core materials of sodium ion batteries and determine the key performance indicators of sodium ion batteries. Compared with layered oxide materials and Prussian blue cathode materials, polyanion materials have comprehensive advantages such as higher safety, lower cost, and longer life, and have received widespread attention. Among them, sodium iron pyrophosphate, a composite phosphate with a chemical composition of abundant and widely available sodium, iron, and phosphorus and a NASICON crystal structure, has a suitable operating voltage (3.1V vs. Na+ / Na), a high theoretical capacity (up to about 129mAh / g), an open three-dimensional framework, and safety and non-toxicity, and is considered to have the greatest application potential.
[0004] However, composite sodium iron phosphate (hereinafter referred to as NFPP, conventionally: Na4Fe3(PO4)2P2O7) has defects such as low intrinsic conductivity and impurities in the synthesis process, which leads to its low rate performance and poor cycle performance, which seriously restricts its commercial application. In view of the above problems, current research mainly focuses on introducing crystal defects and improving carbon coating. Author: Cao Yuliang, Zhao Along, Yuan Tianci, Zhou Xi, Ai Xinping, Yang Hanxi. Title: A Na4Fe 3-x(PO4)2P2O7 / C sodium ion battery positive electrode material and its preparation method and application, discloses that NFPP with different proportions of iron defects is synthesized by non-stoichiometric ratio design, which improves the conductivity of the material, and further reduces the proportion of impurities in the material, improving the rate performance of the material; Author: Zhang Yean, Sun Xuewen, Lai Yanqing, Wang Taosheng, Zhang Kai, Hong Bo, Li Jie. Title: A fluorine-doped carbon-coated sodium iron phosphate pyrophosphate @ mesoporous carbon composite material and its preparation and application in sodium ion batteries, discloses that a layer of fluorine-doped carbon is uniformly coated on the surface of NFPP by simple ball milling and solid phase sintering, and the coating of fluorine-doped carbon effectively improves the stability of NFPP material, thereby improving its cycle performance.
[0005] However, even with the above-mentioned methods such as introducing defects and modifying the coated carbon layer, the rate and cycle performance of NFPP materials still cannot fully meet the requirements of large-scale applications, and the problem of impurities in the synthesis process still exists. Summary of the invention
[0006] The purpose of this application is to provide a sodium ion polycathode positive electrode material synthesized by a solid phase method and a preparation method thereof in view of the deficiencies of the current technology. Compared with NFPP, the sodium ion polycathode positive electrode material synthesized by the solid phase method of this application - sodium iron fluorophosphate (NFPF) is easier to synthesize into a pure phase, and the material generation reaction is easier to carry out. Therefore, the preparation method of this application adopts a solid phase method to prepare a high-purity phase NFPF. In addition, the PF structure in NFPF can effectively reduce the crystal band gap of the material, thereby increasing the probability of electron transition, and then improving its rate performance. At the same time, the interaction between F and Fe can enhance the structural stability and improve its cycle performance.
[0007] In the first aspect, the present application provides a sodium ion polycathode positive electrode material synthesized by a solid phase method, adopting the following technical scheme: a sodium ion polycathode positive electrode material synthesized by a solid phase method, the sodium ion polycathode positive electrode material is sodium iron fluorophosphate (NFPF), and the chemical composition of the sodium iron fluorophosphate (NFPF) is: Na4+xFe3+yP4O12+zFγ, wherein the range of x is -0.1≤x≤0.1; the range of y is -0.1≤y≤0.1; the range of z is 0<z≤-1; the range of γ is 0<γ≤2.
[0008] By adopting the above technical scheme, the sodium ion polycathode positive electrode material synthesized by the solid phase method of the present invention - sodium ferric fluorophosphate (NFPF) is different from the current Na4Fe 3-x P4O 12 Compared with the (NFPP) polyanion positive electrode material, its anion group is a polyhedral anion group composed of phosphorus and oxygen. 4-x F x ) m n- and (P2O7-x F x ) m n- The two share corners or edges to form a stable polyanion skeleton. Compared with NFPP sodium ion positive electrode material, NFPF introduces electronic polarization of chemical bonds, triggering an inductive effect, allowing sodium ions to conduct rapidly in an open framework during the electrochemical process, and making NFPF have a higher redox potential. Therefore, the NFPF prepared in this application has high ionic and electronic conductivity. In addition, the interaction between F and Fe can enhance structural stability and improve its cycle performance.
[0009] Preferably, the composite stabilizer is composed of modified binaphthylthiourea, chromium chloride and thiodipropionic acid in a mass ratio of 5:1:2-4.
[0010] In a second aspect, the present application provides a method for preparing a sodium ion polycathode positive electrode material synthesized by a solid phase method, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned sodium ion polycathode positive electrode material synthesized by a solid phase method, comprising the following steps: According to the ratio of elements in the chemical composition of the sodium ferric fluorophosphate (NFPF), a sodium source compound, an iron source compound, a phosphorus source compound, a fluorine source compound and a carbon source compound are uniformly mixed, a solvent is added and mixed uniformly, and the mixture is sand-milled to a specified particle size, spray-dried, and calcined in a protective atmosphere to prepare the sodium ferric fluorophosphate (NFPF).
[0011] By adopting the above technical scheme, the sodium ion polyanion positive electrode material - sodium ferric fluorophosphate (NFPF) prepared by the solid phase method of the present application has an anion group that is a polyhedral anion group composed of phosphorus and oxygen. 4-x F x ) m n- and (P2O 7- x F x ) m n- The two share corners or edges to form a stable polyanion skeleton. Compared with NFPP sodium ion positive electrode material, NFPF introduces electronic polarization of chemical bonds, triggering an induction effect, allowing sodium ions to conduct rapidly within an open framework during the electrochemical process, and making NFPF have a higher redox potential. Therefore, the NFPF prepared in the present application has high ionic and electronic conductivity. In addition, the interaction between F and Fe can enhance structural stability, make it easy to synthesize a pure phase, and make the material generation reaction easier. The preparation method of the sodium ion polyanion positive electrode material synthesized by the solid phase method of the present application is suitable for large-scale production applications.
[0012] Preferably, the sodium source compound is selected from one or more of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium nitrate, sodium fluoride, sodium fluorophosphate, sodium trifluoroacetate, sodium oxalate, sodium acetate, sodium persulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, sodium dihydrogen pyrophosphate and sodium alginate.
[0013] Preferably, the iron source compound is selected from one or more of reduced iron powder, ferroferric oxide, ferric oxide, ferrous oxide, ferric nitrate, ferric chloride, ferric sulfate, ferric phosphate, ferric oxalate, ferrous oxalate, ferrous acetate, ferric citrate and ferric fluoride.
[0014] Preferably, the phosphorus source compound is selected from one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium dihydrogen pyrophosphate, phosphoric acid, ammonium dihydrogen phosphate and triammonium phosphate.
[0015] Preferably, the fluorine source compound is selected from one or more of fluorophosphoric acid, hydrofluoric acid, sodium monofluorophosphate, sodium difluorophosphate, sodium fluoride, ammonium fluoride, ammonium monofluorophosphate, ammonium difluorophosphate, trifluoroacetic acid, sodium trifluoroacetate and ferric fluoride.
[0016] Preferably, the carbon source compound is selected from one or more of glucose, sucrose, citric acid, malic acid, polyaniline, polyethylene glycol, adipic acid, phenolic resin, polypyrrole, ascorbic acid, chitosan and soluble starch.
[0017] Preferably, the solvent is selected from one or both of water and ethanol, and preferably the solvent is a solution consisting of ethanol and water in a molar ratio of 1:1.
[0018] Preferably, the sand grinding to a specified particle size is wet grinding with a sand grinder to a particle size of 0-400 nm; preferably, the particle size is 150 nm.
[0019] Preferably, the protective atmosphere is one of an inert gas and an argon-hydrogen mixture, and the volume content of hydrogen in the argon-hydrogen mixture is 5%; the process conditions for calcination are a temperature of 400-600° C., preferably 500° C., and a calcination time of 8-12 hours.
[0020] In summary, the beneficial technical effects of this application are: 1. High ionic and electronic conductivity: By introducing electronic polarization of chemical bonds, an inductive effect is induced, which enables sodium ions to conduct rapidly within an open framework during the electrochemical process. This characteristic enables NFPF to have a higher redox potential, thereby improving the energy density and power density of the battery.
[0021] 2. Structural stability: The interaction between F and Fe can enhance the structural stability, so that the material has better structural retention ability during the cycle process, thereby extending the service life of the battery.
[0022] 3. Easy to synthesize pure phase: The solid phase preparation method of the present application makes it easy to synthesize NFPF in pure phase, reducing production costs and facilitating large-scale production applications.
[0023] 4. Environmental protection: Compared with traditional lithium-ion batteries, sodium-ion batteries have better environmental protection performance. Sodium resources are abundant and cheap, and sodium-ion batteries do not produce toxic and harmful substances during use, which is environmentally friendly.
[0024] 5. Safety: Sodium-ion batteries are safer than lithium-ion batteries. Sodium ions have a larger radius and are not easily embedded in the graphite layers, thus reducing the risk of battery short circuits. In addition, sodium-ion batteries have a relatively low risk of thermal runaway under abnormal conditions such as overcharging and overdischarging.
[0025] 6. Easy to mass produce: The solid phase synthesis process of the present application is simple, easy to control, and suitable for large-scale production applications. This method does not require complex equipment and conditions, reduces production costs, and improves the feasibility of industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments: Figure 1 It is a charge and discharge curve diagram of the battery assembled with the sodium ion polycathode positive electrode material synthesized by the solid phase method prepared in Comparative Example 1 and Examples 1 to 3. DETAILED DESCRIPTION
[0027] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] Example 1 A sodium ion polycathode material Na4Fe synthesized by solid phase method 2.92 P4O 11.6 F 0.08The preparation method comprises the following steps: weighing 0.4 mol sodium bicarbonate, 0.292 mol ferric nitrate, 0.1 mol ammonium dihydrogen phosphate, 0.08 mol ammonium fluoride and 0.02 mol glucose in proportion, and dissolving these materials in a water / ethanol (the molar ratio of ethanol to water is 1:1) solution; then transferring the raw materials to a sand mill, wet sand milling at a speed of 2000 r / min, and spray drying after grinding for 3 hours (particle size 150 nm) to obtain a solid powder; placing the solid powder in a tubular furnace in an atmosphere of hydrogen-argon mixed gas (hydrogen volume content is 5%), and sintering at 550°C for 10 hours. The obtained solid product is the sodium ion polycathode positive electrode material synthesized by the solid phase method.
[0029] Example 2 A sodium ion polycathode material Na4Fe synthesized by solid phase method 1.46 P4O 11.6 F 0.08 The preparation method comprises the following steps: weighing 0.4 mol sodium bicarbonate, 0.146 mol iron oxide, 0.1 mol ammonium dihydrogen phosphate, 0.08 mol ammonium fluoride and 0.02 mol glucose in proportion, and dissolving these materials in a water / ethanol (the molar ratio of ethanol to water is 1:1) solution; then transferring the raw materials to a sand mill, wet sand milling at a speed of 2000 r / min, and spray drying after grinding for 3 hours (particle size 150 nm) to obtain a solid powder; placing the solid powder in a tubular furnace in an atmosphere of hydrogen-argon mixed gas (hydrogen volume content is 5%), and sintering at 550°C for 10 hours. The obtained solid product is the sodium ion polycathode positive electrode material synthesized by the solid phase method.
[0030] Example 3 A sodium ion polycathode material Na4Fe synthesized by solid phase method 1.46 P4O 11.7 F 0.06 The preparation method comprises the following steps: weighing 0.4 mol sodium bicarbonate, 0.146 mol iron oxide, 0.1 mol ammonium dihydrogen phosphate, 0.06 mol ammonium fluoride and 0.02 mol glucose in proportion, and dissolving these materials in a water / ethanol (the molar ratio of ethanol to water is 1:1) solution; then transferring the raw materials to a sand mill, wet sand milling at a speed of 2000 r / min, and spray drying after grinding for 3 hours (particle size 150 nm) to obtain a solid powder; placing the solid powder in a tubular furnace in an atmosphere of hydrogen-argon mixed gas (hydrogen volume content is 5%), and sintering at 550°C for 10 hours. The obtained solid product is the sodium ion polycathode positive electrode material synthesized by the solid phase method.
[0031] Example 4 The same as Example 3, except that the solid powder is placed in a tubular furnace with an atmosphere of hydrogen-argon mixed gas (hydrogen content of 5% by volume) and sintered at 400° C. for 12 hours.
[0032] Example 5 The same as Example 3, except that the solid powder is placed in a tubular furnace with an atmosphere of hydrogen-argon mixed gas (hydrogen content of 5% by volume) and sintered at 600° C. for 8 hours.
[0033] Comparative Example 1 A sodium ion polycathode material Na4Fe synthesized by solid phase method 2.92 P4O 12 The preparation method comprises the following steps: weighing 0.4 mol sodium bicarbonate, 0.292 mol ferric nitrate, 0.1 mol ammonium dihydrogen phosphate and 0.02 mol glucose in proportion, and dissolving these materials in a water / ethanol (the molar ratio of ethanol to water is 1:1) solution; then transferring the raw materials to a sand mill, wet sand grinding at a speed of 2000 r / min, grinding for 3 hours (particle size 150nm), spray drying, and obtaining solid powder; placing the solid powder in a tubular furnace in an atmosphere of hydrogen-argon mixed gas (hydrogen volume content is 5%), and sintering at 550°C for 10 hours. The obtained solid product is the sodium ion polycathode positive electrode material synthesized by the solid phase method.
[0034] Performance Testing The sodium ion polycathode positive electrode materials synthesized by the solid phase method prepared in Examples 1 to 3 and Comparative Example 1 were sampled and tested as follows. The test results are shown in Table 1.
[0035] The particle size of the sodium ion polycathode positive electrode material was tested by a laser particle size analyzer (DLS), and the specific surface area was tested by a Best Instruments fully automatic nitrogen adsorption BET specific surface area tester BSD-BET400; Battery performance test: The sodium ion polycathode positive electrode materials synthesized by the solid phase method obtained in Examples 1 to 3 and Comparative Example 1 were respectively made into the following sodium ion batteries: The sodium ion polycathode material, conductive agent Super P and carboxymethyl cellulose were mixed with water in a ratio of 8:1:1 to form a slurry, stirred for 24 hours, coated on carbon-coated aluminum foil, and dried in an oven at 80°C for 24 hours. The dried electrode was cut into 12mm discs with a loading of 1-1.4mg / cm 2 , using sodium foil as the counter electrode, pressed into a sodium ion battery. Charge and discharge test conditions: 1C rate, constant current charge and discharge, voltage range 0.01V to 3.70V. Test results are shown in Table 1 and Figure 1 shown.
[0036] Table 1 Performance test Analyzing the data in Table 1, we can see that: The performance test results of the sodium ion polycathode positive electrode material synthesized by the solid phase method obtained in Example 1-Example 3 show that the sodium ion polycathode positive electrode material synthesized by the solid phase method of the present application - sodium iron fluorophosphate (NFPF) is easier to synthesize into a pure phase than NFPP, and the material generation reaction is easier to carry out. Therefore, the preparation method of the present application adopts the solid phase method to prepare high-purity NFPF. At a 1C rate, the discharge specific capacity after 5000 cycles is more than 105mAh / g, and the capacity retention rate is more than 90.7%.
[0037] The comparative analysis of the performance of the sodium ion polycathode positive electrode materials synthesized by the solid phase method obtained in Example 3 and Comparative Example 1 shows that the PF structure in NFPF can effectively reduce the crystal band gap of the material, thereby increasing the probability of electron transition and further improving its rate performance. At the same time, the interaction between F and Fe can enhance the structural stability and improve its cycle performance.
[0038] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A sodium ion polycathode positive electrode material synthesized by a solid phase method, characterized in that: The sodium ion polycathode positive electrode material is sodium ferric fluorophosphate (NFPF), and the chemical composition of the sodium ferric fluorophosphate (NFPF) is: Na 4+x Fe 3+y P4O 12+z F γ , where the range of x is -0.1≤x≤0.1; the range of y is -0.1≤y≤0.1; the range of z is 0<z≤-1; and the range of γ is 0<γ≤2.
2. A method for preparing a sodium ion polycathode positive electrode material synthesized by a solid phase method according to claim 1, characterized in that: According to the ratio of elements in the chemical composition of the sodium iron fluorophosphate (NFPF), a sodium source compound, an iron source compound, a phosphorus source compound, a fluorine source compound and a carbon source compound are uniformly mixed, a solvent is added and mixed uniformly, and the mixture is sand-milled to a specified particle size, spray-dried, and calcined in a protective atmosphere to prepare the sodium iron fluorophosphate (NFPF).
3. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The sodium source compound is selected from one or more of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium nitrate, sodium fluoride, sodium fluorophosphate, sodium trifluoroacetate, sodium oxalate, sodium acetate, sodium persulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, sodium dihydrogen pyrophosphate and sodium alginate.
4. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The iron source compound is selected from one or more of reduced iron powder, ferroferric oxide, ferric oxide, ferrous oxide, ferric nitrate, ferric chloride, ferric sulfate, ferric phosphate, ferric oxalate, ferrous oxalate, ferrous acetate, ferric citrate and ferric fluoride.
5. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The phosphorus source compound is selected from one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium dihydrogen pyrophosphate, phosphoric acid, ammonium dihydrogen phosphate and triammonium phosphate.
6. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The fluorine source compound is selected from one or more of fluorophosphoric acid, hydrofluoric acid, sodium monofluorophosphate, sodium difluorophosphate, sodium fluoride, ammonium fluoride, ammonium monofluorophosphate, ammonium difluorophosphate, trifluoroacetic acid, sodium trifluoroacetate and ferric fluoride.
7. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The carbon source compound is selected from one or more of glucose, sucrose, citric acid, malic acid, polyaniline, polyethylene glycol, adipic acid, phenolic resin, polypyrrole, ascorbic acid, chitosan and soluble starch.
8. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The solvent is selected from one or both of water and ethanol.
9. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The sand grinding to a specified particle size is wet grinding with a sand grinder to a particle size of 0-400 nm.
10. The sodium ion polycathode positive electrode material synthesized by solid phase method according to claim 2, characterized in that: The protective atmosphere is one of an inert gas and an argon-hydrogen mixed gas, and the volume content of hydrogen in the argon-hydrogen mixed gas is 5%; the process conditions of the calcination are a temperature of 400-600° C. and a calcination time of 8-12 hours.
Citation Information
Patent Citations
Fluorine-doped carbon-coated phosphate ferric sodium pyrophosphate @ mesoporous carbon composite material and preparation thereof and application in sodium ion battery
CN110061233A
Na4Fe3-x(PO4)2P2O7 / C sodium ion battery positive electrode material as well as preparation method and application thereof
CN112768673A
Sodium-rich fluorine-doped ferric sodium pyrophosphate composite material as well as preparation method and application thereof
CN116281922A
Fluorine-doped iron-based mixed pyrophosphate sodium ion battery positive electrode material and preparation and application thereof
CN116666590A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN117239120A
Cited By
Sodium ferric fluorophosphate positive electrode material as well as preparation method and application thereof
CN120573676A